Purification and properties of a novel quizalofop-p-ethyl-hydrolyzing esterase involved in quizalofop-p-ethyl degradation by Pseudomonas sp. J-2 - Hui Zhang; Mengya Li; Jie Li; Guangli Wang; Yuan Liu (Microbial Cell Factories, 2017)
Abstract Quizalofop-p-ethyl (QPE) is a post-emergence herbicide that effectively controls grass weeds and is often detected in the environment. However, the biochemical and molecular mechanisms of QPE degradation in the environment remains unclear. In this study, a highly effective QPE-degrading bacterial strain J-2 was isolated from acclimated activated sludge and identified as a Pseudomonas sp., containing the QPE breakdown metabolite quizalofop acid (QA) identified by Liquid Chromatography-Ion Trap-Mass Spectrometry (LC-IT-MSn) analysis. A novel QPE hydrolase esterase-encoding gene qpeH was cloned from strain J-2 and functionally expressed in Escherichia coli BL21 (DE3). The specific activity of recombinant QpeH was 198.9 ± 2.7 U mg−1 for QPE with K m and K cat values of 41.3 ± 3.6 μM and 127.3 ± 4.5 s−1. The optimal pH and temperature for the recombinant QpeH were 8.0 and 30 °C, respectively and the enzyme was activated by Ca2+, Cd2+, Li+, Fe3+ and Co2+ and inhibited by Ni2+, Fe2+, Ag+, DEPC, SDS, Tween 80, Triton X, β-mercaptoethanol, PMSF, and pCMB. In addition, the catalytic efficiency of QpeH toward different AOPP herbicides in descending order was as follows: fenoxaprop-P-ethyl > quizalofop-P-tefuryl > QPE > haloxyfop-P-methyl > cyhalofopbutyl > clodinafop-propargyl. On the basis of the phylogenetic analysis and multiple sequence alignment, the identified enzyme QpeH, was clustered with esterase family V, suggesting a new member of this family because of its low similarity of amino acid sequence with esterases reported previously.